Three trap designs evaluated for a deepwater lionfish fishery - Harris, Holden E.; Garner, Steven B.; Tarnecki, Joseph H.; Gittings, Stephen R.; Chagaris, David D.; Patterson, William F. (Frontiers in Marine Science, 2023)
A deepwater (>40 m) fishery for invasive lionfish (Pterois volitans/miles) offers a potential means to control invasive lionfish densities and mitigate their impacts on reefs too deep for SCUBA removals. Trapping could provide a scalable solution—if an effective fishing gear with minimal environmental impacts could be permitted and adopted by fishers. We tested the efficacy of wooden slat lobster traps, wire sea bass traps, and experimental non-containment Gittings traps. One hundred deployments of each trap type were made at 120 mesophotic (38–78 m deep) natural reef sites in the northeastern Gulf of Mexico (29.6–30.1°N, 86.1–87.6°W). Reef sites were surveyed with remotely operated vehicles (ROV) before and after trap deployments, and remote time-lapse video cameras were affixed above 86 traps to sample in situ recruitment to the traps. The video data showed that lionfish were attracted to the vicinity of the three trap types at similar rates, but that lionfish rarely entered the lobster or sea bass traps. The high bycatch rates of sea bass traps suggested their use is likely unsuitable for targeting lionfish. Lobster traps had lower rates of bycatch, but their relatively high ratio of bycatch-to-lionfish catches suggests that modifications will be needed to make them more efficient. The Gittings traps had the highest lionfish catch rates and lowest bycatches of native fishes, but operational issues were also identified. They failed to open on 20% of deployments and one entangled a green sea turtle (Chelonia mydas). Even with the best-performing trap design, the average catch rate of lionfish was less than one lionfish per trap. A potential explanation could be the low biomass of lionfish observed during the ROV surveys, which averaged 0.3 kg lionfish per site. The time-lapse video data suggested that lionfish recruitment to Gittings traps could increase with higher densities of lionfish on the nearby reefs, if traps were retrieved after approximately two days of deployment, and if traps were retrieved during dawn or dusk. Further research, development, and testing is needed for lionfish traps, and critical bio- and techno-economic assessments appear warranted to evaluate the feasibility of a deepwater lionfish fishery.